ʺImplementation of European experience in ensuring ethics and academic integrity in educational and research activities - Bachiieva , L.O. (Problems of Engineer-Pedagogical Education, 2023)
In the world educational and scientific community, a clear understanding of what is interpreted as «academic integrity» has been formed. This is a set of fundamental values that are the basis of educational and research activities. Among them, the following should be identified: honesty, trust, justice, respect, responsibility and others. An academic environment grounded on these values is the basis or the foundation that promotes the development of education and science through the implementation of honesty and integrity. Ensuring compliance with academic integrity in education is possible under the condition of systematic work based on current recommendations and experience. In the first chapter, based on the provisions of the Law of Ukraine «On Education», the Draft Law «On Academic Integrity», the Law of Ukraine «On Copyright and Related Rights», we define the essence of the concept of «academic integrity» and the interpretation of key terms associated with it. In the second section, recommendations on combating academic dishonesty are presented, which include such aspects as prevention of fraud in education; prosecuting persons who have violated the rules of academic integrity; the flow of international cooperation to solve this problem, etc. Findings show that subjects of the educational process have access to regulatory information on ethics and academic integrity in educational and research activities; effective mechanisms for preventing dishonesty in education are the creation of an academic environment that promotes compliance with relevant principles. It is based on defined zero-tolerance policies for academic and research fraud; creative, practically oriented tasks that reveal models of the specialist's future professional activity; clearly defined and published quantitative and qualitative criteria for evaluating tasks; effective interaction between the subjects of educational and research work based on the principles of ethics. It was determined that higher education students and teaching (research and teaching) staff are actively involved in international projects dedicated to the researched issue. The conclusions reflect scientific generalizations of the application of European experience in ensuring ethics and academic integrity in educational and research activities in education institutions of Ukraine.